Patients performing lower limb exercises in an orthopedic ward: a best practice implementation project. Issue 3 (22nd September 2021) - Koh, Siew Yi; Sridaran, Mahendran N.; Goh, Mien Li
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Aims: The evidence-based project sought to educate patients on doing lower limb exercises within 24 h of their admissions to the ward. Patients spend most of their time in bed during their hospital stays, which imposes negative outcomes due to inactivity, such as risks of reduced muscle mass and deconditioning, which may further implicate patients' conditions. Methods: The project occurred in three phases over a period of 18 months. The project was undertaken in an orthopedic ward of an acute tertiary hospital. A preimplementation and postimplementation audit strategy using the Joanna Briggs Institute's Practical Application of Clinical Evidence System was conducted on a sample of 20 adult patients. The Getting Research into Practice framework was utilized to analyze the barriers and gaps encountered in the clinical ground. Results: The baseline audit result revealed that only 35% of the patients received education on the exercise program and that there was poor compliance on nursing documentation of the intervention in daily note-free texts. Following the implementation, there was an improvement in nurses' documentation compliance. In follow-up audits one and two, the nurses achieved compliance rates of 60 and 90% in nursing documentation, respectively. Conclusion: Overall, there were improvements in provision of lower limb exercise education to patients. This project has demonstrated that patients were willing to exercise during hospitalization. Nurses play a significant role in providing early education to patients to do simple exercises. The implementation of the evidence-based project may increase the awareness of the importance of exercises to minimize hospital-acquired deconditioning and functional declines among ward nurses and patients.